China - Hong, F. (Comparative elite sport development. Systems, structures and public policy, 2025)
After the modern Olympic movement was introduced to China at the beginning of the twentieth century, a seminar organised in October 1908 by the Tianjin YMCA raised the well-known `Three Questions about the Olympics: When would China send its first athlete to participate in the Olympic Games? When would Chinese athletes win their first gold medal at the Olympic Games? When would the Olympic Games be held in China?` (Hong et al., 2008). China spent the next 100 years finding the answers to these questions.